AUDIO TRANSPORT APPROACHS TROUGH IP NETWORKS IN THE CONTEXT OF THE TRUNKING RADIO SYSTEM MPT-1327 - Yáñez de la Rivera, René; de Villegas Biosca, Brian Joffre; Alpizar Aguiar, Julio A. (Telemática, 2021)
The Radio Trunking System MPT-1327 is an analogical technology with digital control, developed by the United Kingdom in the 80 decades, being considered by operators high valuable equipment because of its performance and sturdiness. This explains that some operators wish to extend the useful life cycle of the system, but are facing troubles because of obsolescence of equipment set, especially the denominated Megaplex Gateways, which have in charge the access to SDH transport networks, besides, the proper trends of the network to IP (Internet Protocol). A unique commercial available solution is possible from RAD enterprise from Israel with a branch in the USA, a condition that can be against some policies of operators who prefer more independence from suppliers. Furthermore, in the case of Cuba, the embargo is a strong obstacle. The purpose of this report is to accomplish a theoretical study of solutions approaches to be implemented by either commercial solutions, own development, or a hybrid combination of them. The premise for this analysis is to study the features of Megaplex platforms taking into account working principles, performance, and evolution, being this the key equipment in relation. An analysis of alternative solutions is carried out considering criteria of cost, acquisition feasibility, and development contributing to set a priority order and suggesting strategies to different situations.